Trigeminal nerve-driven neurogenic inflammation linking migraine to glioblastoma invasion: a literature review - Xiaoli Song; Xiaoli Song; Qian Zhu; Qian Zhu; Jieying Zhang; Jieying Zhang; Jin Yang; Jin Yang; Xinxin Zhang; Xinxin Zhang; Qian Song; Qian Song (Frontiers in Immunology)
Migraines are among the most common neurological disorders, disabling nearly one in seven people worldwide, whereas glioblastoma (GBM) is the most aggressive primary brain tumour, with median survival scarcely beyond 15 months. Historically considered distinct, these conditions are increasingly linked by trigeminal nerve-driven neurogenic inflammation. Activation of trigeminovascular afferents provokes antidromic release of calcitonin gene-related peptide (CGRP), substance P (SP), and pituitary adenylate cyclase-activating polypeptide (PACAP); beyond mediating migraine pain, these peptides remodel vasculature, immune infiltrates, and extracellular matrix to facilitate GBM invasion. Pre-clinical studies show CGRP and SP up-regulate matrix-metalloproteinases and integrins, while PACAP modulates cAMP–MAPK signalling, collectively promoting perivascular migration and temozolomide resistance. Epidemiological analyses report higher migraine antecedents in patients later diagnosed with brain tumours, and high-resolution MRI frequently localises GBM spread along trigeminal pathways, underscoring anatomical plausibility. Emerging therapeutics mirror these insights: aprepitant (an NK1-receptor antagonist) triggers GBM apoptosis, gepant-class CGRP blockers curb invasive phenotypes, and radiolabelled SP analogues deliver focal alpha-therapy. These discoveries facilitate more precise pathogenetic characterisation, reduce diagnostic uncertainty, and expedite translational drug development. This review synthesises current evidence on trigeminal neurogenic inflammation as a mechanistic conduit between migraine biology and GBM progression, mapping cellular circuits, molecular crosstalk, and translational interventions. By integrating neurobiology, oncology, and pharmacology, we aim to delineate diagnostic blind spots, spotlight drug-repurposing opportunities, and chart a roadmap toward personalised strategies that simultaneously alleviate migraine burden and restrain glioblastoma aggressiveness.